From Research to Memes: The Enduring Stereotypes of Upernavimmiutut - Kleemann-Andersen, Camilla (Études Inuit Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2024)
Kalaallit Nunaat has a tradition of broadcasting a New Year’s show on KNR-TV to mock the past year and the national political scandals. The show often parodies people from different towns, imitating their dialect. Irvine and Gal’s (2000) concept of processes of language ideologies (iconization, erasure, and fractal recursivity,) alongside Agha’s enregisterment (2003) shows how a dialect can become more marginalized by using features with negative connotations. The article analyses how the media is a tool to reproduce stereotypes and contribute to maintaining the power structures in society by using normalized humour that mocks dialects. The Upernavimmiutut dialect is used as a case study. Coloniality is still visible in today’s Kalaallit Nunaat, and it affects marginalized groups. Standardization and mediatization (Androutsopoulos 2014) also play a significant role in maintaining the power structures in the linguistic arena. The article looks at how people in power have reproduced language ideologies over the decades and how democratized new media maintain them by distributing them through research, TV, and memes in social media.